1971
DOI: 10.2514/3.6489
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study of a two-dimensional turbulent wall jet in a movingstream with arbitrary pressure gradient

Abstract: Measurements of flow parameters for a two-dimensional turbulent wall jet are presented in a range of ratios of slot stream velocity to external stream velocity with pressure gradients, not previously investigated. These data are utilized for the calculations of wall shear and shear distribution by numerical methods. Relationships among the parameters are considered. Nomenclature= similarity function for velocity profile in the jet layer in initial region /fe) = similarity function for velocity profile in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A number of basic investigations were conducted by Eskinazi and Kruka [4], Kruka and Eskinazi [5], Patel and Newman [6], Goradia and Colwell [7], and Kacker and Whitelaw [8] on plane turbulent compound wall jets. It may be concluded from their findings that the velocity profile in the boundary layer and free-mixing regions are similar if considered separately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of basic investigations were conducted by Eskinazi and Kruka [4], Kruka and Eskinazi [5], Patel and Newman [6], Goradia and Colwell [7], and Kacker and Whitelaw [8] on plane turbulent compound wall jets. It may be concluded from their findings that the velocity profile in the boundary layer and free-mixing regions are similar if considered separately.…”
Section: Introductionmentioning
confidence: 99%
“…It may be concluded from their findings that the velocity profile in the boundary layer and free-mixing regions are similar if considered separately. Goradia and Colwell [7], and Erian and Eskinazi [9] found that, even with pressure gradients, similarity of velocity profiles exists if each distinct region is considered separately.…”
Section: Introductionmentioning
confidence: 99%